(3GdQMeI aj GdWH hGdMceIs - (3eMeO GdegOj Hf EHQGgje GdUHjQj Gdjefj GdgfOj,J (B815 (3g` s ((3eMeO GdTQja GdeSGcfi GddbH GdGYhQ s)
(3ChdgG (B:s
(3hHYO agPG cJGH eNJUQ hVYJg aj Yde GdWH , hgPHJ GeQGVg hbQHJ GZQGVg, hLYdJg LGeYkG aj MGdg GdGNJUGQ , djQhb HEfLGRI GdbdhH hGdCHUGQ, hjSgd eJfGhdI ddWGdH hOQSg hMaXg ddQGZH s
(3BNQgG (B:s
(3hdojYGhO GdeSgd cd ESHhY eQI Ch ai GdTgQ eQJjf Gh eQI Ydi bOQ VYa GdTNU hbhJg aEfg fGaY UMjM oeLQH hGddg CYde hgPG eG CQOfG hEdjg bUOfG ef cJGHfG GdeQShe HcJGH GdQMeI ai GdWH hGdMceI s
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B100 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B((3O (B1121) s
Keywords: (3GdWHs